STRATEGI PEMASARAN DALAM MENINGKATKAN DAYA SAING USAHA GROSIR BERAS TOKO BERAS HIDAYAT - Tia Nanda Sari; Jumriah Basri (PIRSAP (Paser Institute for Scientific Research and Publications), 2025)
This study aims to determine the marketing strategies implemented by Toko Beras Hidayat in enhancing the competitiveness of its rice wholesale business. The research also seeks to analyze the influence of marketing strategies on competitiveness, identify the constraining factors encountered, and examine the efforts and solutions undertaken to overcome these challenges.The research method used is descriptive qualitative, with data collected through observation, interviews, and documentation. The data obtained were analyzed qualitatively to describe the actual conditions in the field.The results of the study indicate that Toko Beras Hidayat applies a marketing strategy based on the marketing mix, which includes product, price, place, and promotion. This strategy has proven effective in enhancing business competitiveness through increased sales, customer loyalty, and a positive business image. However, several challenges remain in its implementation, such as rice price fluctuations, limited capital, intense competition among wholesalers, and insufficient digital promotion.To address these challenges, Toko Beras Hidayat has undertaken various efforts, including establishing direct cooperation with rice mills, expanding promotions through social media, maintaining product quality, and diversifying its business. With adaptive and innovative strategies, Toko Beras Hidayat has been able to maintain its existence and enhance its competitiveness in the rice wholesale market.